2021
DOI: 10.12968/ajmw.2020.0017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of male involvement in maternal healthcare services in southwest Nigeria

Abstract: Background/Aims In Nigeria, women's partners are often excluded from taking part in maternal healthcare, as a result of sociocultural norms. However, the involvement of male partners in maternal healthcare services has the potential to improve maternal health outcomes. This study examined factors associated with male involvement in maternal healthcare services in Ife Central, Osun State, Nigeria. Methods A cross-sectional study was conducted, involving 265 men living in Ife Central who were married with at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…Generally, married men and those within monogamous family arrangements demonstrated elevated levels of involvement in contrast to single fathers and those from polygamous family setups. Similar findings have been widely documented in the past studies where stable and monogamous unions have been linked with increased level of male partner's involvement (14,23,33,34). Men in stable and monogamous unions may experience a more conducive environment for shared responsibilities leading to greater participation in pregnancy care.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Generally, married men and those within monogamous family arrangements demonstrated elevated levels of involvement in contrast to single fathers and those from polygamous family setups. Similar findings have been widely documented in the past studies where stable and monogamous unions have been linked with increased level of male partner's involvement (14,23,33,34). Men in stable and monogamous unions may experience a more conducive environment for shared responsibilities leading to greater participation in pregnancy care.…”
Section: Discussionsupporting
confidence: 90%
“…Also, it may signify an alignment with progressive societal values that recognize and encourage men's active roles in reproductive health, thereby fostering a culture of inclusive and collaborative pregnancy care practices. Although this study found that most of the study participants expressed positive attitudes towards supportive behaviors, perceived challenges to active involvement included traditional gender norms, social stigma, ridicule, unconducive health facility environment and exclusion of men from maternity care activities in agreement with evidence from earlier investigations ( 5 , 11 , 20 , 31 , 33 , 34 , 39 42 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations